Inflation is Always and Everywhere a Monetary Phenomenon: Richmond vs. Houston in 1864 - Richard C.K. Burdekin; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 1999)
On April 1, 1864 the Confederate Currency Reform Act reduced the money supply in the Eastern Confederacy by one third. The delayed implementation of the reform west of the Mississippi provides a counterfactual view of what may have happened in the east had the reform not been enacted. This episode is a natural experiment illustrating the relative importance for prices of war news vs. the quantity of money in circulation. Our analysis of the major eastern and western gold markets, Richmond and Houston, strongly suggests that money matters more than war news in the post-reform period.
Keywords: N20; N40; 330; Confederacy; currency reform; quantity theory